2019
DOI: 10.32854/agrop.v0i0.1348
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de biofertilizantes a base de microorganismos y lixiviado de vermicomposta en cultivos de interés económico en México

Abstract: Objetivo: Caracterizar el efecto de un biofertilizante a base de lixiviado vermicomposta (VCL) en cultivos de relevancia en México, formulado en combinación con: i) fertilizante químico (NPK), ii) una mezcla de dos productos comerciales con microorganismos promotores del crecimiento de las plantas y hongos micorrízicos arbusculares (HMA) y iii) melaza. Diseño/metodología/aproximación: Cuatro tratamientos fueron evaluados: T1 (VCL, microorganismos, sin melaza y sin NPK), T2 (VCL, microorganismos, sin mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Favorable results have been obtained with the use of these organic products, as is the case of rice production (Oryza sativa L.) with manure tea (Diaz and Contreras, 2022), hybrid maize (Zea mays) under the application of biocompost and vermicompost (Fortis-Hernández et al, 2009), maize (Zea mays), tomato (Solanum lycopersicum), chili (Capsicum annuum), sorghum (Sorghum bicolor), common bean (Phaseolus vulgaris), pea (Pisum sativum), pumpkin (Cucurbita pepo) and watermelon (Citrullus lanatus) with leachate of vermicompost and soil microorganisms, which decreased the dose of chemical fertilization by up to 35 % (Guardiola-Márquez et al, 2019). Alvarado et al (2017) concluded in their study, that the use of mycorrhizal-based biofertilizer in common beans achieved increases of 15 %, in the number of pods and grain weight per plant, as well as the yield per hectare.…”
Section: Introductionmentioning
confidence: 99%
“…Favorable results have been obtained with the use of these organic products, as is the case of rice production (Oryza sativa L.) with manure tea (Diaz and Contreras, 2022), hybrid maize (Zea mays) under the application of biocompost and vermicompost (Fortis-Hernández et al, 2009), maize (Zea mays), tomato (Solanum lycopersicum), chili (Capsicum annuum), sorghum (Sorghum bicolor), common bean (Phaseolus vulgaris), pea (Pisum sativum), pumpkin (Cucurbita pepo) and watermelon (Citrullus lanatus) with leachate of vermicompost and soil microorganisms, which decreased the dose of chemical fertilization by up to 35 % (Guardiola-Márquez et al, 2019). Alvarado et al (2017) concluded in their study, that the use of mycorrhizal-based biofertilizer in common beans achieved increases of 15 %, in the number of pods and grain weight per plant, as well as the yield per hectare.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of sustainable agriculture is a viable alternative to meet these challenges as it involves the development of cost effective, eco-friendly and high efficiency procedures (Malusá et al, 2012;DeLonge et al, 2016;Busby et al, 2017;Prasad et al, 2017;El-Ghamry et al, 2018;Adisa et al, 2019;Elemike et al, 2019;Kumari and Singh, 2019). The use of biofertilizers is a very promising sustainable practice since they improve water use efficiency, increase crop yields from 10 to up to 40 % (Bhardwaj et al, 2014), reduce chemical fertilization (35 to 50 %) without compromising crops yield (Kumar et al, 2009;Isfahani and Besharati, 2012;Aggani, 2013;Saeed et al, 2015a, b;Nurbaity et al, 2016;Guardiola-Márquez et al, 2019), and improve plant resistance to adverse environmental conditions (Jochum et al, 2019;Ojuederie et al, 2019). Beneficial microorganisms from biofertilizers colonize the rhizosphere and root system of the plant and promote growth through different mechanisms such as siderophores production, atmospheric nitrogen fixation, solubilization of minerals (phosphorus, potassium), and production of phytohormones (auxins, cytokinins, gibberellins) and enzymes (phosphatases, catalases) (Vessey, 2003;Bardi and Malusa, 2012;Malusa and Vassilev, 2014;Alori et al, 2017;Mahanty et al, 2017;El-Ghamry et al, 2018;Gouda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that biofertilizers can save up to 50% of synthetic fertilizers [4,33]. Positive effects from different microorganisms have been reported for laboratory and greenhouse experiments [16,17,[34][35][36][37][38]. However, the potential of biofertilizers for decreasing synthetic fertilizer rates and or increasing the yield of cereals under field conditions in Mexico has been limited and unclear.…”
Section: Introductionmentioning
confidence: 99%